On the Distribution Efficiency of an Optimal Monetary Policy - Preechametta, Arayah (Thammasat Review of Economic and Social Policy, 2017)
The paper studies the impacts of an optimal monetary policy on the distribution and production efficiencies by using a framework of multiple types of household and assets. It extends the work of Xiang (2013) by adding a new type of risky asset, known as Lucas tree, into an existing moneybond model. Some new results can be generated by requiring that all asset markets must satisfy the non-arbitrage profit condition. For example, regardless of insufficient liquidity, a zero nominal interest rate as suggested by the Friedman rule becomes an optimal monetary policy that can lead the economy to its full distribution efficiency and also lower its production inefficiency at the same time.